A nanosensor for in vivo selenol imaging based on the formation of AuSe bonds. (June 2016) - Hu, Bo; Cheng, Ranran; Liu, Xiaojun; Pan, Xiaohong; Kong, Fanpeng; Gao, Wen; Xu, Kehua; Tang, Bo
Abstract: Selenol is a key metabolite of Na2 SeO3 and plays an important role in many physiological and pathological processes. The real-time monitoring of selenol is of scientific interest for understanding the anti-cancer mechanism of Na2 SeO3 . Based on selenol's ability to specifically break AuS bonds and form more stable AuSe bonds on the surfaces of gold nanoparticles (AuNPs), we developed a novel near-infrared fluorescent nanosensor (Cy5.5-peptide-AuNPs) for detecting selenol. The nanosensor exhibited rapid response to selenol with high selectivity and sensitivity, and it was successfully used to image changes in the selenol level in HepG2 cells during Na2 SeO3 -induced apoptosis. Moreover, in vivo fluorescence imaging of selenol was obtained from H22 tumor-bearing mice injected with both the nanosensor and sodium selenite. The results showed that the tumor cell apoptosis induced by Na2 SeO3 is correlated with high-level of selenol under hypoxic conditions. We believe that this nanosensor could serve as a powerful tool for monitoring selenol and exploring the physiological function of selenol in a variety of physiological and pathological contexts and that the probe-designed strategy will provide a new platform for research on relevant selenium chemistry. Graphical abstract: